Efektivitas Blended learning dan Diskusi-Presentasi Terhadap Hasil Belajar Ditinjau dari Kemampuan Verbal-Lingustic Mahasiswa - Ansori, Miksan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Blended learning is a new method and deemed in accordance with the current ICT developments. In addition to the need for study on the method, blended learning is also felt able to answer the problem of the lack of learning in university that still rely discussion-presentation teaching. This study has the aim to determine whether the results of student learning with blended learning method is better than the method of discussion-presentation viewed from verbal-linguistic ability. This study uses a quantitative approach to the type of quasi- experimental, by trying out of a treatment. Techniques hypothesis testing using analysis of variance (ANOVA) two ways with a 2 x 2 factorial (α = 5%) and the prerequisite test used is the average similarity test, test of normality and homogenity test. The results obtained are (1) the results of student learning with blended learning method is better than the results of student learning with the method of discussion-presentation. (2) There is significant influence levels of verbal-linguistic toward student learning outcomes and (3) the results of student learning with blended learning method is better than the the results of student learning with the method of discussion-presentation, both for students with high or low verbal-linguistic abilities.